Perlindungan Terhadap Perempuan Korban Prostitusi Online - Arie Benedict Pardede (Universitas Medan Area, 2020)
This research aims to find out. Prostitution in Indonesia is considered a crime against decency and against the law. The issue is focused on the criminal provisions on online prostitution in Indonesia, aspects of legal protection against women as victims of online prostitution crimes, local government policies in the protection of women victims of online prostitution crimes. in this matter is used approach to legal protection theory and criminal policy theory. The data was collected through normative juridical legal research methods, where the approach to the problem uses a statutory approach to the criminal law of women victims of online prostitution and is analyzed qualitatively. The study concluded that a new law would be needed to take care of victims, by establishing regulations that could ensnare users of online prostitution services. The role of the police and judges to provide restitution and rehabilitation rights to TPPO victims is very important efforts to restore security for TPPO victims. The participation of local governments, especially the Provincial Government of North Sumatra through the women's and children's protection services responded to the issue of legal reform by issuing regional regulations on the protection of women and children from acts of violence is not enough because the government is more impressed pasih in the form of its services.